Trial by Dutch laboratories for evaluation of non‐invasive prenatal testing. Part II—women's perspectives†. (16th November 2016) - van Schendel, Rachèl V.; Page‐Christiaens, G. C. (Lieve); Beulen, Lean; Bilardo, Catia M.; de Boer, Marjon A.; Coumans, Audrey B. C.; Faas, Brigitte H.; van Langen, Irene M.; Lichtenbelt, Klaske D.; van Maarle, Merel C.; Macville, Merryn V. E.; Oepkes, Dick; et al.
Abstract: Objective: To evaluate preferences and decision‐making among high‐risk pregnant women offered a choice between Non‐Invasive Prenatal Testing (NIPT), invasive testing or no further testing. Methods: Nationwide implementation study (TRIDENT) offering NIPT as contingent screening test for women at increased risk for fetal aneuploidy based on first‐trimester combined testing (> 1:200) or medical history. A questionnaire was completed after counseling assessing knowledge, attitudes and participation following the Multidimensional Measure of Informed Choice. Results: A total of 1091/1253 (87%) women completed the questionnaire. Of these, 1053 (96.5%) underwent NIPT, 37 (3.4%) invasive testing and 1 (0.1%) declined testing. 91.7% preferred NIPT because of test safety. Overall, 77.9% made an informed choice, 89.8% had sufficient knowledge and 90.5% had positive attitudes towards NIPT. Women with intermediate (odds ratio (OR) = 3.51[1.70–7.22], p < 0.001) or high educational level (OR = 4.36[2.22–8.54], p < 0.001) and women with adequate health literacy (OR = 2.60[1.36–4.95], p = 0.004) were more likely to make an informed choice. Informed choice was associated with less decisional conflict and less anxiety ( p < 0.001). Intention to terminate the pregnancy for Down syndrome was higher among women undergoing invasive testing (86.5%) compared to those undergoing NIPT (58.4%) ( p < 0.001). Conclusions: The majority of women had sufficient knowledge and made an informed choice. Continuous attention for counseling is required, especially for low‐educated and less health‐literate women. © 2016 The Authors. Prenatal Diagnosis published by John Wiley & Sons, Ltd. Abstract : What's already known about this topic? NIPT is offered as alternative to invasive testing to screen pregnant women at high risk for fetal aneuploidy. Although NIPT has many advantages, concerns have been raised about the consequences for informed decision‐making. What does this study adds? Implementation of NIPT in a national healthcare‐funded prenatal screening program, accompanied by pre‐test counseling, results in most women having sufficient knowledge and making an informed choice Compared to women choosing invasive testing, women undergoing NIPT have less intention to terminate the pregnancy for Down syndrome.